SIMULTANEOUS SURGICAL TREATMENT OF PATIENTS WITH PRIMARY MULTIPLE SYNCHRONOUS KIDNEY AND PROSTATE CANCER - N. V. Vorobev; A. A. Krasheninnikov; F. S. Ashyrova; P. V. Golubev; Yu. V. Samsonov; A. D. Kaprin (Исследования и практика в медицине)
Presently primary-multiple malignancies are still poorly studied and represent a complex problem in clinical Oncology. The frequency of occurrence of primary-multiple metachronous or synchronous tumors remains at a high level. It is worth noting that about 1.5% of patients with primary multiple tumors had a malignant neoplasm of the prostate. Performing simultaneous laparoscopic operations allow to achieve rapid postoperative rehabilitation of the patient, to avoid the risk of re-operation and anesthesia, in addition, there is a clear economic benefit, there is no need for re-examination and preoperative preparation. This article demonstrates two clinical cases of simultaneous surgical treatment of patients with primary multiple tumors of the kidney and prostate.